THE DEVELOPMENT OF BOOKS SEARCHING INFORMATION SYSTEM BY USING THESAURUS BASED ON SHORT MESSAGE SERVICE (SMS) IN GANESHA UNIVERSITY OF EDUCATION LIBRARY IN SINGARAJA - Avendias Mahawan, I Made (Universitas Pendidikan Ganesha, 2013)
Ganesha University of Education (UNDIKSHA) is one of the universitiesthat have the vision and mission create the qualified of educators.and noneducators, to achieve that vision UNDIKSHA need good facilities to support student learning, one of these facilities is the library. The library is a information centre, source of knowledge, research and recreation UNDIKSHA Library has thousands of books by different authors and has been supported by a good system to help students in finding information, The main factors is a student does not find the books that need at the library's collections and students become lazy to come to the library because the books they want to borrow is not return yet. This studyis aimed to create and implementate a software Searching Books Information System by Using Thesaurus based on Short Message Service (SMS) in Ganesha Universitiy of Education (UNDIKSHA) Library in Singaraja. The application is expected to assist members in obtaining information about books in UNDIKSHA Library. Information Systems Development is using a waterfall model, designed by Data Flow Diagram (DFD) and implemented by PHP programming language and MYSQL as the database and Gammu to run the SMS Gateway. After the testing process, it can be concluded that this application is capable to give information about books in library, the existence of the books in library, the date of returning the books for users who borrow the books and reminder of returning the books which is sent by SMS.